Optimal nitrogen management to sugarcane production in different harvest seasons - Souza Netto, Gerson José Marquesi de (2019)
Sugarcane is harvested during nine months per year in Brazil with a wide range of water balance that ultimately affect response to nitrogen (N). However, a single N rate of approximately 1.1 kg N per Mg of sugarcane produced is used over the harvest season, applied as a single application few weeks after sugarcane harvest. In addition, there is a trend of growers to increase N rates in the green cane trash blanketing system (GCTB) of Brazil. This study aimed to test the hypothesis that optimal N management will be achieved by means of ascertaining N rates in each harvest season through split instead of single application. Five field trials were conducted in each harvest season (autumn: April to June; winter: July to September; and spring: October to December) across center-south region of Brazil in the 2016/2017 crop season. The experimental design was a N response curve with the N rates being defined according the yield obtained in the previous season (0.8; 1.0; 1.2 and 1.4 kg N per Mg sugarcane; plus an additional control); additional treatments with split N application were tested in autumn and winter, but not in spring. Sugarcane harvested during autumn presented higher response to N when compared to areas harvested in winter or spring. Higher responsiveness to N can be related to the lower water deficit suffered from sites harvested during autumn. Split application showed a limited but positive potential in increasing yields by 2.3 Mg ha-1 during autumn, but not in winter. Nitrogen rates of 1.0, 0.8, and 0.8 kg N Mg-1 can be recommended for sugarcane areas harvested respectively in autumn, winter and spring of center south, Brazil. The finding of this study is that optimal N management should consider the harvest time to ascertain N rates for profitable sugarcane production.